Olimpiyat oyunlarina katilmaya aday boksörlerin covid-19 kaygi düzeylerinin incelenmesi - Öktem, T.; Sipal, O.; Kul, M.; Dilek, A. N. (International Journal of Social and Humanities Sciences Research, 2020)
The aim of this study is to examine the anxiety levels of the boxing national team Olympic staff formed for the Tokyo 2020 Olympic Games qualifiers in terms of various variables. The data in the study were obtained by collecting data with questionnaires. The population of the research consists of 30 boxers in the Tokyo 2020 Olympic Games qualifiers squad. Sampling was not used because the entire universe was reached. The state and trait anxiety scale developed by Spielberger, Gorsuch and Lushene (1970) was used. The Turkish reliability and validity study of the scale was conducted by Öner and Le Compte (1985). The trait anxiety dimension of the scale was used. The analysis of the data was done using the SPSS 22 package program. In descriptive data analysis; One-way analysis of variance and Independent Sample T-test was performed with the analyzes aimed at determining the mean, standard deviation, frequency and percentage. Although it was determined that the trait anxiety scores of the Olympic boxers did not show a statistically significant difference according to the results obtained from the study, according to the gender variable, it was observed that female boxers had higher averages than male boxers. Asa result; It can be said that this situation is caused by the fact that female boxers are weaker in cognitive, physical and psychological aspects compared to male boxers.